3D ZnO rod‐like structures loaded with silver nanoparticles and their enhanced photocatalytic performance. (1st December 2017) - Wang, Qiang; Yu, Zhuanni; Sun, Xiaowei; Lan, Jing
Abstract : Three‐dimensional (3D) zinc oxide (ZnO) rod‐like structures loaded with silver (Ag) nanoparticles (3D Ag/ZnO RLS) have been successfully synthesised by a facile hydrothermal and microwave method. The successful loading of Ag nanoparticles and the 3D hierarchical structure were characterised by scanning electron microscopy and X‐ray diffraction. The pHs of zero point charge were 7.8 and 7.9 for 3D ZnO rod‐like structures (3D ZnO RLS) and 3D Ag/ZnO RLS, respectively. The photocatalytic performances of the 3D RLS were evaluated by decomposing methylene blue under ultraviolet irradiation. Compared to 3D ZnO RLS, the enhanced photocatalytic performance of 3D Ag/ZnO RLS may be attributed to the 3D hierarchical structure of the Ag/ZnO, as the structure can lead to enhanced light absorption and lower recombination of photoinduced holes and electrons.